Dental Erosion, Splitting Labial and Palatal Indirect Resin Composite Veneers: Review Literature and A Case Report - Kunawarote, Sitthikorn; Khuankaew, Chutikul; Cherdstirakul, Piriya (Chiang Mai Dental Journal, 2018)
Modern life styles are various, resulting in increasing incident of behavioral related diseases. Paranormal nutritional habits, for instant increased intake of acidic juices or carbonic beverages, as well as acidic medications, gastro-esophageal reflux disease, or eating disorders, environmental exposure to acidic fumes or swimming pool water are some of the causative resulting in erosive tooth wear. Dental erosion is characterized by pathological loss of dentition structure as a consequence of the chemical dissolution of mineral content in dental hard tissue. Intrinsic or extrinsic erosive causing factors are related to site and characteristic of lesions. Erosive lesions are basically affecting patient dentition integrity and esthetics, mostly starting with teeth hypersensitivity and progressing to loss of vertical dimension or vitality of dentition. This article addressed the principle of diagnosis and disease assessment for dental erosion and also the treatment options. Moreover, the case report represented the patient with severe dental erosion due to long-term contacted to acidic swimming pool water, resulting teeth hypersensitivity, worn out of enamel and dentin which is affected dentition dimension and appearance. In this case, the splitting labial and palatal indirect resin composite veneer has been a treatment of choice regarding it simplicity, cost-effective and preservation of dental structure as well.